MUŞ İLİNDEN DERLENEN MANİLER ÜZERİNE BİR İNCELEME - ELİTOK, NEVİN (Fırat Üniveristesi, 2006)
Muş İlinden Derlenen Mâniler Üzerine Bir İnceleme adlı çalışmamızda mâninin tarihî gelişimi ve menşei incelenerek mâni ile türkü, ağıt, ninni, bilmece, atasözü, deyim, dua, beddua ilişkisi ele alınarak benzer ve farklı yönler tespit edilmiştir. Çalışmamızda derleme işinin özellikleri hakkında bilgi vererek, mânilerin derlenmesiyle ilgili düşüncelerimizi belittik. Ayrıca mânilerle ilgili yapmış olduğumuz bir tasnifin yanında edebiyatımızda mâniler üzerine yapılan bazı tasnif çalışmalarına da yer verdik. Muş ilinden ve ilçelerinden derlediğimiz 795 mâniyi inceleyerek şekline ve temalarına göre tasnif ettik. Yaptığımız tasnifte derlediğimiz mânilerden örnekler vererek çalışmamızı zenginleştirdik. Çalışmamızın sonunda derlediğimiz 795 mâniyi birinci mısralarının ilk harflerine göre alfabetik olarak düzenli bir şekilde verdik. ANAHTAR KELİMELER: Mâni, Şekil, Tema.

In this study, titled "An Examination of Mani Collected from Mus City Region", following the evaluation of historical development and origin of mani, similarities and dissimilarities of mani with its relation to folk song, dirge, lullaby, riddle, proverb, idiom, prayer and curse were determined. In our study, providing knowledge about characteristics of eclectic process, we emphasized our opinions on the collection of mani. Moreover, not only we included some classification of mani performed by us but also some other studies on the classification mani in the literature. We examined and classified 795 manies collected form Muş City and its boroughs according to their formation and theme. We enriched our study giving examples from our collected manies of the classification. Seven-hundred and ninetyfive manies collected at the end of our study were given as in alphabetical order according to their first letter of the first line of poetry. KEY WORDS: Mani, Form, Theme
An examination of mani collected from Muş city region
Keywords: Türk Dili ve Edebiyatı